Histomorphological Profile of Colonoscopic Biopsies and Pattern of Colorectal Carcinoma in Kavre District - Rajbhandari, M; Karmacharya, A; Khanal, K; Dhakal, P; Shrestha, R (Kathmandu University Medical Journal, 2015)
Background Colonoscopy is the method to visualize the mucosa of the entire colon and terminal ileum to detect the intestinal abnormalities and obtain biopsy for definitive diagnosis. For clinical decisions in the diagnosis of various colonic lesions unambiguous interpretation of colorectal biopsies is necessary. Objectives To assess the prevalence pattern of colonic diseases and to correlate the incidence of colorectal carcinoma with age, sex, site and symptoms presented at Dhulikhel Hospital. Methods The materials consisted of 126 biopsies which were submitted to the Department of Pathology, Kathmandu University School of Medical Sciences, Dhulikhel, during the period of July 2011- July 2012 .Data collected and entered in MS-Excel and were analyzed using SPSS-16. Results Out of 126 colonoscopic biopsies 34(27%) showed chronic nonspecific inflammation, followed by carcinoma 25(19.8%), non-neoplastic polyps 21(16.7%), granulomatous inflammation 14(11.1%), neoplastic polyps 8(6.3%), ulcerative colitis 4(3.2%) Miscellaneous lesions; Acute focal colitis, Eosinophilic colitis were also observed in 19 (15.1%). A higher frequency of colonic diseases in males with a male to female ratio of 1.4:1 and age range of two years to 84 years was observed. Out of 25 patients diagnosed with colorectal carcinoma,48% (n=12) were males and 52% (n=13) were females with a mean age of 55.17 years in men and 59.46 years in females. Male and female ratio among cancer groups was 1:1.08. Total 36% (n=9) were diagnosed with cancer before the age of 50. Out of these nine cases, 6( 66.7%) were males and 3(33.3%) were females. The male and female ratio in younger and older age groups were 2:1 and 1:1.7 . 17( 68%) of the lesions were left sided and 8(32%) were right sided. Below age 50 , left to Right sided lesions in males were 2:1 and in females 1:2. However, above 50 years the ratio among proximal and distal lesions were 5:1 in males and 2.3:1 in females. A statistically significant association was seen between the growth (p=0.000) and per rectal bleeding (p= 0.006) with carcinoma. Conclusion The most prevalent lesion in colorectal biopsies was non-specific colitis followed by carcinoma colon. The incidence of colorectal carcinoma is on rise in Nepalese society. Although colorectal carcinoma is more common in older age group the incidence are also increasing among young especially among women. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12503 Kathmandu Univ Med J 2013; 43(3):196-200